An Exploratory Study of Student Persistence and its Relationship with Achievement While Using a Game-based Learning Environment - Palaoag, Thelma D (Archīum Ateneo, 2015)
This study tests the common wisdom that persistence leads to academic success. We explore indicators or markers of persistence exhibited by 60 students from Baguio City, Philippines as they played a game-based learning environment called Physics Playground. The study attempted to determine the extent to which the markers of persistence identified by Shute et al. (2013) – specifically time spent, number of level restarts, and number of level revisits – were related with achievement. When clustered the data into two, according to these features, the clusters only differed significantly in terms of time spent and number of restarts. Number of revisits was not significantly different. What was most interesting, though, was that gold and no-badge outcomes were significantly negatively correlated with time spent and significantly positively correlated with number of restarts. These findings imply Shute’s markers while possibly indicative of persistence may also be indicative of non-learning behaviors, most notably wheel spinning.